Influence of certain factors on rainfall frequency values - TRIPATHI, N. (MAUSAM, 1976)
Based on 84-Year data of Calcutta, Delhi, Bombay and Madras, it has been found that to estimate to the maximum one-day point rainfall for long return periods, more reliance is to be placed on stations with the longest records. For error to be within 25 per cent in about 80 per cent of cases, in the estimation of return period values excluded from the series. Criteria to find the outline have been found suggested. Some evidence has been found to show that the return period values of rainfall of a station increase with in air pollution at that station.